2021
DOI: 10.1002/slct.202101560
|View full text |Cite|
|
Sign up to set email alerts
|

Radical Scavenging Efficiency of Flavonoids Increased by Calcium(II) Binding: Structure‐Activity Relationship

Abstract: Six structurally related flavonoids including two flavones apigenin and luteolin, one isoflavone genistein, and three flavonols, galangin, kaempferol and quercetin, are affected differently as radical scavengers by presence of Ca(II). Except for apigenin showing no reaction with Ca(II), other flavonoids all coordinate with Ca(II) to form 1 : 2 Ca(II)‐flavonoid complexes confirmed by UV‐vis and mass spectra. Coordination with Ca(II) for luteolin with the 3′, 4′‐catechol group and for flavonols with 3‐hydroxyl a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Similarly, the ABTS⋅ + kinetics of 5 μM CA, 5 μM GA, and CAT with 50 μM Ca(II) and Mg(II) also showed minimal alterations (Figures 3d–f). This suggests that there is no reaction occurring between polyphenols and Ca(II) or Mg(II), despite their concentrations being in the range of 1–10 mM, which has been reported to significantly enhance the antioxidant activity of flavonoids [15–16] …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, the ABTS⋅ + kinetics of 5 μM CA, 5 μM GA, and CAT with 50 μM Ca(II) and Mg(II) also showed minimal alterations (Figures 3d–f). This suggests that there is no reaction occurring between polyphenols and Ca(II) or Mg(II), despite their concentrations being in the range of 1–10 mM, which has been reported to significantly enhance the antioxidant activity of flavonoids [15–16] …”
Section: Resultsmentioning
confidence: 97%
“…A significant body of research, including our recent work, has highlighted that the radical scavenging capacity of polyphenols, a key indicator of their antioxidant activity, is substantially altered when these compounds interact with metal ions. These interactions occur not only with transition metal ions such as Cu(II) and Zn(II) but also with main group metal ions like Ca(II), Mg(II), and Al(III) [13–17] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 A large number of studies including our recent work have shown that the radical scavenging ability as one of the main indicators of the antioxidant activity of flavonoids is significantly enhanced in a homogeneous ethanol or aqueous model system when the flavonoids are combined with metal ions like Cu(II) and Zn(II) and alkaline earth metal ions including Ca(II), Mg(II), Sr(II), and Ba(II). 9 12 …”
Section: Introductionmentioning
confidence: 99%
“…The physiological activities of flavonoids are mainly attributed to their antioxidant activities including radical scavenging, metal chelation, as well as enzymatic activity inhibition in forming reactive oxygen species (ROS) . A large number of studies including our recent work have shown that the radical scavenging ability as one of the main indicators of the antioxidant activity of flavonoids is significantly enhanced in a homogeneous ethanol or aqueous model system when the flavonoids are combined with metal ions like Cu­(II) and Zn­(II) and alkaline earth metal ions including Ca­(II), Mg­(II), Sr­(II), and Ba­(II). …”
Section: Introductionmentioning
confidence: 99%